The V4: a Decade after the EU Entry - Eduard Nežinský; Elena Fifeková (Entrepreneurial Business and Economics Review)
The objective of the paper is to give a picture of the sources of economic growth in the V4 countries during the decade following their EU entry and to crosscheck the results obtained by parametric and non-parametric approaches. Growth accounting technique is used to depict dynamics of the V4 countries evolution since 1995 up to 2013. The poor post-crisis performance reflected in TFP indicator is in line with the result of the absence of technological progress obtained by data envelopment analysis.